APOPHATIC THEOLOGY: PSEUDO-DIONYSIUS AND THOMAS AQUINAS - MENDIS, B SANJEEWA MAHESHE (Innovare Journal of Social Sciences, 2024)
Dionysius’s apophatic theology developed the basic tenets necessary for a deeper focus on God in Christian theology. The confusion it caused in Christian theology was powerfully presented through the investigations presented by the Neo-platonic philosophers. Furthermore, despite various interpretations of these teachings since the time of the Church Fathers, Pseudo Dionysius correctly presented the need to establish a correct foundation for it. His teachings were the foundation for later theological interpretations. This study examines the apophatic theology presented by Pseudo- Dionysius and Saint Thomas Aquinas. It is expected to investigate the facts presented using the analytical research method. Apophatic theology can be used to approach God by denying that any theological concept of God can be properly established by rejecting all the ideas and images of the theology laid by Dionysius and by entering into the divine darkness beyond understanding. A central theme of Aquinas’s apophatic philosophy is that we can know God more by what he is not than by what he is. Apophatic theology is also seen as an affirmation of the inadequacy of human understanding of divine matters. It is seen as affirming God’s essence through ignorance, even though man is aware through God’s energies.